P131 Role of cryoprotectants and seminal plasma in the fertility of cooled-stored donkey (Equus asinus) semen - A.C. Silva; C.Z. dos Santos; M. Marchetti; H. Hitson; R. Almeida; F.P. Lisboa; G.A. Monteiro; M.A. Alvarenga; L. Segabinazzi (Journal of Equine Veterinary Science, 2026)

Limited functional compensation among subunits of the carbonic anhydrase module of mitochondrial complex I - Nehuen Balestieri; Fernanda Marchetti; Ana Caroline P. Martins; Danilo M. Daloso; Gabriela Pagnussat; Juan Pablo Córdoba; Eduardo Zabaleta (Planta, 2026)

Application of error-corrected sequencing technologies for in vivo regulatory mutagenicity assessment - Carole L. Yauk; Anthony M. Lynch; Vasily N. Dobrovolsky; Maik Schuler; Stephanie L. Smith-Roe; Devon Fitzgerald; Jake Higgins; Naveed Honarvar; Frank Le Curieux; Shoji Matsumura; Sheroy Minocherhomji; Leslie Recio; et al. (Regulatory Toxicology and Pharmacology, 2026)

Nourish: The User Experience - M. Hesse; T. Marchetti; J. Walsh; K. Good (Journal of the Academy of Nutrition and Dietetics, 2025)

P09-36 The toxicological effects of ultrafine particles (UFP) resulting from the combustion of fossil-based fuels and bio-fuels in an atmospheric simulation chamber - S. Marchetti; G. Motta; V. Vernocchi; G. De Falco; M. Commodo; A. D'Anna; T. Isolabella; D. Massabò; P. Minutolo; P. Prati; P. Mantecca; M. Gualtieri (Toxicology Letters, 2025)

Temporal analyses of germ cell mutations using the MutaMouse model support the recommended design in OECD test guideline 488 - Gu Zhou; Andrew Williams; Danielle P. M. LeBlanc; George R. Douglas; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2025)
The Organisation for Economic Co-operation and Development test guideline (TG) 488 uses transgenic rodent models to assess in vivo mutagenesis. TG 488 recommends 28 consecutive days of exposure with sampling of germ cells from seminiferous tubules 28 days post-exposure (i.e., 28 + 28d). We analyzed mutant frequencies (MF) in male germ cells up to 70 days post-exposure to determine whether designs other than 28 + 28d are necessary for assessing germ cell mutagenicity. Adult MutaMouse males received various doses of benzo(a)pyrene (BaP), N -ethyl- N -nitrosourea (ENU), isopropyl methanesulfonate (iPMS), or procarbazine (PRC) alongside vehicle controls for 28 days orally. Germ cells were collected from seminiferous tubules at + 3d, + 28d, + 42d, or + 70d post-exposure and MF quantified using the lacZ assay. Significant increases in lacZ MF were observed for all four chemicals at 28 + 28d. No further increases occurred at later sampling times. There was no significant effect with BaP at 28 + 3d, and a significantly stronger response with ENU and BaP at 28 + 28d compared to 28 + 3d. PRC produced the strongest response at 28 + 3d, while there was no impact of different sampling times for iPMS. Both these chemicals significantly reduced testis weight at 28 + 3d and 28 + 28d. Finally, benchmark dose modeling generated overlapping confidence intervals among the four sampling times for ENU, iPMS, and PRC. However, for BaP, the confidence interval was significantly greater at 28 + 3d than at the other sampling times. These results support the use of the 28 + 28d design as the recommended experimental design for germ cells in TG 488 and that later sampling times are not necessary.

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Drivers of Marine Phytoplankton Diversity and Connectivity in the Galápagos Archipelago Spanning an ENSO Cycle - Prisca Lim; Harvey Seim; Oliva Torano; Erika Neave; Se Hyeon Jang; Zackary Johnson; Sara Haines; Scott Gifford; Natalie Cohen; Carly M. Moreno; Margarita Lankford; Cristina Vintimilla Palacios; et al. (Environmental Microbiology, 2025)
The Galápagos Islands are a biodiversity hotspot, largely due to the Equatorial Undercurrent (EUC) which supplies nutrient‐rich waters to the euphotic zone and supports enhanced levels of primary productivity performed by phytoplankton. Understanding phytoplankton responses to changing environmental conditions is crucial for regional conservation and management efforts. Research cruises conducted between 2014 and 2022, spanning a major El Niño event in 2015 and a La Niña event in 2022, observed varying oceanic conditions and diverse phytoplankton community composition. At most EUC‐influenced stations, larger‐sized phytoplankton groups (≥ 5 μm) were dominant while warmer, oligotrophic sites favoured smaller‐sized phytoplankton groups (

Predicting invasiveness of freshwater fishes imported into North America: regional differences in models and outcomes - Jennifer G. Howeth; Sarah A. Amjad; Crysta A. Gantz; Nicholas E. Mandrak; Paul L. Angermeier; Michael P. Marchetti; Julian D. Olden; David M. Lodge (Biological Invasions, 2025)
Biological invasions driven by international trade heighten the urgency for development of invasion risk models, as the traits and parameters that consistently predict successful invasion remain unresolved. For four regions of North America that include parts of the United States and Canada (Sacramento-San Joaquin River Basins, Lower Colorado River Basin, Great Lakes Region, Mid-Atlantic Region), we construct and compare classification tree models to reveal robust predictors for the establishment and ecological impact stages of freshwater fish invasion. We subsequently apply the models to identify invasive fish species in trade and conduct pathway analyses to determine which trades (aquarium, biological supply, live bait, live food, water garden) and source continents pose the greatest risk to each region. Model results differed by invasion stage and region. Across regions, establishment models shared climate-related predictors including climate match and temperature tolerance. Three of the four impact models contained prior establishment success. The greatest number of species (548) were predicted to establish in the Sacramento-San Joaquin while the fewest (5) were predicted to establish in the Mid-Atlantic. Forty species were predicted to establish in multiple regions, five of which were also predicted to have high impact. The aquarium trade and Asia supplied the most species predicted to establish. Taken together, the results highlight region-specific models, indicating no universal model predicts invasion. Climate-related and prior establishment variables were most useful to risk assessments. The regional models, and identified high-risk pathways and potential invaders, could be applied to prevent future fish invasions in North America.

Inhalation of nanoplastics in the mouse model: Tissue bio-distribution and effects on the olfactory system - G. Prosperi; N. Marchetti; A. D'Elia; R. Massari; M. Giusto; A. Pietrodangelo; T. Rossi; A. Nucara; F. Scavizzi; G. Strimpakos; S. Marinelli; S. Mandillo; et al. (Science of The Total Environment, 2025)

Theoretical-experimental design of TiO2 photocatalysts for removal of emerging pollutants from water: The effect of Ga doping on photodegradation of methyl orange - Franco Berdini; Herman Heffner; Jorge M. Marchetti; Ignacio López-Corral; Maximiliano Brigante (Journal of Water Process Engineering, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

Enhancing nutrient removal, biomass production, and biochemical production by optimizing microalgae cultivation in a mixture of untreated and anaerobically digested dairy wastewater - Suvidha Gupta; Jorge M. Marchetti; Kailas L. Wasewar (Journal of Water Process Engineering, 2024)

Drought responses of Italian silver fir provenances in a climate change perspective - S.D. Oggioni; L.M.W. Rossi; C. Avanzi; M. Marchetti; A. Piotti; G. Vacchiano (Dendrochronologia, 2024)

A case of feline gastrointestinal eosinophilic sclerosing fibroplasia extending to the liver - M. Orlandi; F. Abramo; V. Habermass; E. Gori; V. Marchetti (Journal of Comparative Pathology, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

The impact of habitat complexity on the structure of marine sessile communities and larvae supply - Otávio C. Marchetti; Silvia Titotto; Gustavo M. Dias (Marine Environmental Research, 2024)

OS01-09: Mitochondrial dysfunction trigerred by air pollution-derived ultrafine particles chronic exposure in the lungs of Balb/cJRj mice - E. Barbier; J. Carpentier; O. Simonin; A. Chaumy; W. Laine; S. Anthérieu; P. Marchetti; J.-M. Lo Guidice; J. Kluza; G. Garçon (Toxicology Letters, 2023)

Duplex sequencing provides detailed characterization of mutation frequencies and spectra in the bone marrow of MutaMouse males exposed to procarbazine hydrochloride - Annette E. Dodge; Danielle P. M. LeBlanc; Gu Zhou; Andrew Williams; Matthew J. Meier; Phu Van; Fang Yin Lo; Charles C. Valentine III; Jesse J. Salk; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2023)
Mutagenicity testing is an essential component of health safety assessment. Duplex Sequencing (DS), an emerging high-accuracy DNA sequencing technology, may provide substantial advantages over conventional mutagenicity assays. DS could be used to eliminate reliance on standalone reporter assays and provide mechanistic information alongside mutation frequency (MF) data. However, the performance of DS must be thoroughly assessed before it can be routinely implemented for standard testing. We used DS to study spontaneous and procarbazine (PRC)-induced mutations in the bone marrow (BM) of MutaMouse males across a panel of 20 diverse genomic targets. Mice were exposed to 0, 6.25, 12.5, or 25 mg/kg-bw/day for 28 days by oral gavage and BM sampled 42 days post-exposure. Results were compared with those obtained using the conventional lacZ viral plaque assay on the same samples. DS detected significant increases in mutation frequencies and changes to mutation spectra at all PRC doses. Low intra-group variability within DS samples allowed for detection of increases at lower doses than the lacZ assay. While the lacZ assay initially yielded a higher fold-change in mutant frequency than DS, inclusion of clonal mutations in DS mutation frequencies reduced this discrepancy. Power analyses suggested that three animals per dose group and 500 million duplex base pairs per sample is sufficient to detect a 1.5-fold increase in mutations with > 80% power. Overall, we demonstrate several advantages of DS over classical mutagenicity assays and provide data to support efforts to identify optimal study designs for the application of DS as a regulatory test.

Error-corrected next generation sequencing – Promises and challenges for genotoxicity and cancer risk assessment - Francesco Marchetti; Renato Cardoso; Connie L. Chen; George R. Douglas; Joanne Elloway; Patricia A. Escobar; Tod Harper; Robert H. Heflich; Darren Kidd; Anthony M. Lynch; Meagan B. Myers; Barbara L. Parsons; et al. (Mutation Research - Reviews in Mutation Research, 2023)

Anti-Müllerian hormone in queens: Serum concentrations and total ovarian follicle population - C. Lapuente; M. Faya; P.G. Blanco; M. Grisolia-Romero; C. Marchetti; C. Gobello (Theriogenology, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Protistan plankton communities in the Galápagos Archipelago respond to changes in deep water masses resulting from the 2015/16 El Niño - Erika F. Neave; Harvey Seim; Scott M. Gifford; Olivia Torano; Zackary I. Johnson; Diego Páez‐Rosas; Adrian Marchetti (Environmental Microbiology, 2022)
Summary The Galápagos Archipelago lies within the Eastern Equatorial Pacific Ocean at the convergence of major ocean currents that are subject to changes in circulation. The nutrient‐rich Equatorial Undercurrent upwells from the west onto the Galápagos platform, stimulating primary production, but this source of deep water weakens during El Niño events. Based on measurements from repeat cruises, the 2015/16 El Niño was associated with declines in phytoplankton biomass at most sites throughout the archipelago and reduced utilization of nitrate, particularly in large‐sized phytoplankton in the western region. Protistan assemblages were identified by sequencing the V4 region of the 18S rRNA gene. Dinoflagellates, chlorophytes and diatoms dominated most sites. Shifts in dinoflagellate communities were most apparent between the years; parasitic dinoflagellates, Syndiniales , were highly detected during the El Niño (2015) while the dinoflagellate genus, Gyrodinium , increased at many sites during the neutral period (2016). Variations in protistan communities were most strongly correlated with changes in subthermocline water density. These findings indicate that marine protistan communities in this region are regimented by deep water mass sources and thus could be profoundly affected by altered ocean circulation.

Numerical Modeling of Infrasound Energy Radiation by Debris Flow Events - M. Coco; E. Marchetti; O. Morandi (Pure and Applied Geophysics, 2021)
Debris flows constitute a severe natural hazard in Alpine regions. Studies are performed to understand the event predictability and to identify early warning systems and procedures. These are based both on sensors deployed along the channels or on the amplitude of seismic and infrasound waves radiated by the flow and recorded far away. Despite being very promising, infrasound cannot be used to infer the source characteristics due to the lack of a physical model of the infrasound energy radiated by debris flows. Here the simulation of water flow along a simple channel is presented, experiencing the fall from a dam, performed within the open source simulation code OpenFOAM. The pressure perturbation within the atmosphere produced by the flow is extracted and the infrasound signature of the events as a function of the flow characteristics is defined. Numerical results suggest that infrasound is radiated immediately downstream of the dam with amplitude and period that scale with dam height and water level. Modeled infrasound waveform is interpreted as being produced mostly by waves at the water free surface developing downstream of the dam. Despite the effect of sediments is not considered in this first study and will be implemented in future investigations, numerical results obtained with this simple model are in general agreement with experimental results obtained from array analysis of infrasound data recorded at Illgraben, Switzerland. Results highlight how numerical modeling can provide critical information to define a source mechanism of infrasound energy radiation by debris-flow, that is required also to improve early warning systems.

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Low diversity of a key phytoplankton group along the West Antarctic Peninsula - Michael S. Brown; Jeff S. Bowman; Yajuan Lin; Colette J. Feehan; Carly M. Moreno; Nicolas Cassar; Adrian Marchetti; Oscar M. Schofield (Limnology and Oceanography, 2021)
The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and biogeochemistry. Here, we use a phylogenetic placement approach with 18S rRNA gene amplicon sequence variants to assess surface ocean cryptophyte diversity and its drivers at a high taxonomic resolution along the Peninsula. Data were collected over 5 years (2012–2016) during the regional research cruises of the Palmer Long‐Term Ecological Research program. Our results indicate that there are two major cryptophyte taxa along the Peninsula, consisting of distinct Geminigera spp., which in aggregate always comprise nearly 100% of the cryptophyte community (indicating low taxa evenness). The primary taxon dominates the cryptophyte community across all samples/years, which span a broad range of oceanographic conditions. A shift in cryptophyte community composition between a lower (higher) primary (secondary) taxon percentage is associated with distinct oceanographic conditions, including lower (higher) temperature, salinity, nutrients, and cryptophyte relative abundance (phytoplankton biomass and diatom relative abundance). These results emphasize the need for a full characterization of the ecology of these two taxa, as it is predicted that cryptophytes will increase along the Peninsula given projections of continued regional environmental change.

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Antifungal activity of oils macerates of North Sardinia plants against Candida species isolated from clinical patients with candidiasis - M.G. Donadu; D. Usai; M. Marchetti; M. Usai; V. Mazzarello; P. Molicotti; M.A. Montesu; G. Delogu; S. Zanetti (Natural Product Research, 2020)

Efficient zinc/cobalt inter‐replacement in northeast Pacific diatoms and relationship to high surface dissolved Co : Zn ratios - Riss M. Kellogg; Matthew R. McIlvin; Jagruti Vedamati; Benjamin S. Twining; James W. Moffett; Adrian Marchetti; Dawn M. Moran; Mak A. Saito (Limnology and Oceanography, 2020)
The importance of zinc (Zn) as a nutrient and its ability to be substituted for by cobalt (Co) have been characterized in model marine diatoms. However, the extent to which this substitution capability is distributed among diatom taxa is unknown. Zn/Co metabolic substitution was assayed in four diatom species as measured by the effect of free ion concentrations of Zn 2+ and Co 2+ on specific growth rate. Analysis of growth responses found substitution of these metals can occur within the northwest Atlantic isolate Thalassiosira pseudonana CCMP1335, the northeast Atlantic isolate Phaeodactylum tricornutum CCMP632, and within the northeast Pacific isolates Pseudo‐nitzschia delicatissima UNC1205 and Thalassiosira sp. UNC1203. Metabolic substitution of Co in place of Zn in the Atlantic diatoms supports their growth in media lacking added Zn, but at the cost of reduced growth rates. In contrast, highly efficient Zn/Co substitution that supported growth even in media lacking added Zn was observed in the northeast Pacific diatoms. We also present new data from the northeast Pacific Line P transect that revealed dissolved Co and Zn ratios (dCo : dZn) as high as 3.52 : 1 at surface (0–100 m) depths. We posit that the enhanced ability of the NE Pacific diatoms to grow using Co is an adaptation to these high surface dCo : dZn ratios. Particulate metal data and single‐cell metal quotas also suggest a high Zn demand in diatoms that may be partially compensated for by Co.

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Interannual radial growth sensitivity to climatic variations and extreme events in mixed-species and pure forest stands of silver fir and European beech in the Italian Peninsula - S. Versace; D. Gianelle; V. Garfì; G. Battipaglia; F. Lombardi; M. Marchetti; R. Tognetti (European Journal of Forest Research, 2020)

Interactive effects of iron and light limitation on the molecular physiology of the Southern Ocean diatom Fragilariopsis kerguelensis - Carly M. Moreno; Weida Gong; Natalie R. Cohen; Kimberly DeLong; Adrian Marchetti (Limnology and Oceanography, 2020)
The polar diatom Fragilariopsis kerguelensis is ubiquitous in Southern Ocean waters and is a major responder to iron fertilization, encountering large gradients in iron concentrations and light availability. We performed a comparative transcriptomic analysis of F. kerguelensis grown under varying iron and light conditions in order to investigate the molecular underpinnings that may explain its physiological response to iron and light limitation. Low iron reduced growth rates more than low light, but there was not an additive effect of low iron and low light on growth rate. Low iron treatments (saturating and low light) had the largest transcriptomic response; however, expression patterns were more similar in low light treatments (high and low iron). Under iron and light limitation, carbon fixation and amino acid, ribosome, and sulfur metabolisms were overrepresented relative to the control (iron replete, saturating light). Transcripts of genes encoding for the proteins aquaporin, proteorhodopsin, plastocyanin, and flavodoxin were overrepresented to the greatest extent in the low iron/low light treatment, indicating there may be an additive effect of iron/light colimitation at the molecular level. Iron and light replete cells demonstrated increased expression of genes encoding for the proteins ferritin, carbonic anhydrase, and numerous iron‐dependent proteins relative to the growth‐limiting treatments. This transcriptome analysis reveals mechanisms that may underpin the ecological success of this diatom in low iron and light environments, highlighting the important role of diversified photosynthetic isoforms, iron acquisition, unique detoxification mechanisms of reactive oxygen species, and metabolic shifts in amino acid recycling and carbon metabolism.

Phase I pharmacological study of continuous chronomodulated capecitabine treatment - Jeroen Roosendaal; Bart A. W. Jacobs; Dick Pluim; Hilde Rosing; Niels de Vries; Erik van Werkhoven; Bastiaan Nuijen; Jos H. Beijnen; Alwin D. R. Huitema; Jan H. M. Schellens; Serena Marchetti (Pharmaceutical Research, 2020)
Purpose Capecitabine is an oral pre-pro-drug of the anti-cancer drug 5-fluorouracil (5-FU). The biological activity of the 5-FU degrading enzyme, dihydropyrimidine dehydrogenase (DPD), and the target enzyme thymidylate synthase (TS), are subject to circadian rhythmicity in healthy volunteers. The aim of this study was to determine the maximum tolerated dose (MTD), dose-limiting toxicity (DLT), safety, pharmacokinetics (PK) and pharmacodynamics (PD) of capecitabine therapy adapted to this circadian rhythm (chronomodulated therapy). Methods Patients aged ≥18 years with advanced solid tumours potentially benefitting from capecitabine therapy were enrolled. A classical dose escalation 3 + 3 design was applied. Capecitabine was administered daily without interruptions. The daily dose was divided in morning and evening doses that were administered at 9:00 h and 24:00 h, respectively. The ratio of the morning to the evening dose was 3:5 (morning: evening). PK and PD were examined on treatment days 7 and 8. Results A total of 25 patients were enrolled. The MTD of continuous chronomodulated capecitabine therapy was established at 750/1250 mg/m 2 /day, and was generally well tolerated. Circadian rhythmicity in the plasma PK of capecitabine, dFCR, dFUR and 5-FU was not demonstrated. TS activity was induced and DPD activity demonstrated circadian rhythmicity during capecitabine treatment. Conclusion The MTD of continuous chronomodulated capecitabine treatment allows for a 20% higher dose intensity compared to the approved regimen (1250 mg/m 2 bi-daily on day 1–14 of every 21-day cycle). Chronomodulated treatment with capecitabine is promising and could lead to improved tolerability and efficacy of capecitabine.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Peripheral and cerebrospinal fluid immune activation and inflammation in chronically HIV-infected patients before and after virally suppressive combination antiretroviral therapy (cART) - E. Merlini; F. Iannuzzi; A. Calcagno; F. Bai; M. Trunfio; A. d’Arminio Monforte; S. Bonora; Giulia Marchetti (Journal of NeuroVirology, 2018)

Transcriptomic and proteomic responses of the oceanic diatom Pseudo‐nitzschia granii to iron limitation - Natalie R Cohen; Weida Gong; Dawn M. Moran; Matthew R. McIlvin; Mak A. Saito; Adrian Marchetti (Environmental Microbiology, 2018)
Summary Diatoms are a highly successful group of photosynthetic protists that often thrive under adverse environmental conditions. Members of the genus Pseudo‐nitzschia are ecologically important diatoms which are able to subsist during periods of chronic iron limitation and form dense blooms following iron fertilization events. The cellular strategies within diatoms that orchestrate these physiological responses to variable iron concentrations remain largely uncharacterized. Using a combined transcriptomic and proteomic approach, we explore the exceptional ability of a diatom isolated from the iron‐limited Northeast Pacific Ocean to reorganize its intracellular processes as a function of iron. We compared the molecular responses of Pseudo‐nitzschia granii observed under iron‐replete and iron‐limited growth conditions to those of other model diatoms. Iron‐coordinated molecular responses demonstrated some agreement between gene expression and protein abundance, including iron‐starvation‐induced‐proteins, a putative iron transport system and components of photosynthesis and the Calvin cycle. Pseudo‐nitzschia granii distinctly differentially expresses genes encoding proteins involved in iron‐independent photosynthetic electron transport, urea acquisition and vitamin synthesis. We show that P. granii is unique among studied diatoms in its physiology stemming from distinct cellular responses, which may underlie its ability to subsist in low iron regions and rapidly bloom to outcompete other diatom taxa following iron enrichment.

Iron storage capacities and associated ferritin gene expression among marine diatoms - Natalie R. Cohen; Elizabeth Mann; Brooke Stemple; Carly M. Moreno; Sara Rauschenberg; Jeremy E. Jacquot; William G. Sunda; Benjamin S. Twining; Adrian Marchetti (Limnology and Oceanography, 2018)
In large regions of the ocean, low iron availability regulates diatom growth and species composition. Diatom species often vary in their physiological response to iron enrichment, with natural and artificial iron additions in iron‐limited regions of the ocean resulting in large blooms of primarily pennate diatoms. The ability of pennate diatoms to proliferate following pulse iron additions has been partly attributed to their ability to acquire and store excess intracellular iron in the iron storage protein ferritin. Recent transcriptome sequencing of diatoms indicate that some centric diatoms also possess ferritin. Using a combination of physiological and molecular techniques, we examined the iron storage capacities and associated ferritin gene expression in phylogenetically diverse centric and pennate diatoms grown under high and low iron concentrations. There were no systematic differences among ferritin‐containing and non‐containing diatom lineages in their ability to store iron in excess of that needed to support maximum growth rates. An exception, however, was the ferritin‐containing pennate diatom Pseudo‐nitzschia granii , native to iron‐limited waters of the Northeast Pacific Ocean. This species exhibited an exceptionally large luxury iron storage capacity and increased ferritin gene expression at high iron concentrations, supporting a role in long‐term iron storage. By contrast, two other diatoms species that exhibited minimal iron storage capacities contained two distinct ferritin genes where one ferritin gene increased in expression under iron limitation while the second showed no variation with cellular iron status. We conclude that ferritin may serve multiple functional roles that are independent of diatom phylogeny.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Examination of gene repertoires and physiological responses to iron and light limitation in Southern Ocean diatoms - Carly M. Moreno; Yajuan Lin; Sarah Davies; Elaine Monbureau; Nicolas Cassar; Adrian Marchetti (Polar Biology, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Anthropogenic impact in the Maya Lowlands of Petén, Guatemala, during the last 5500 years - D. Battistel; M. Roman; A. Marchetti; N. M. Kehrwald; M. Radaelli; E. Balliana; G. Toscano; C. Barbante (Journal of Quaternary Science, 2018)
Trace and rare earth elements from a sediment core from Lake Petén Itzá (Guatemala) depict the geochemical dynamics affecting the lake from ∼5500 a BP to the present. This timing encompasses the Preclassic (4000–1700 a BP) and Classic Periods (1700−1000 a BP) when thriving Maya societies extensively cleared land for agriculture. We demonstrate that this land use occurred during times of increased precipitation, where both processes resulted in increased erosion. Rare earth element ratios depict high precipitation rates between 3000 and 1000 a BP, correlating with an increase in allochthonous silicate input and low organic carbon in the ‘Maya Clay’ stratigraphic section, where this layer is ascribed to intensive anthropogenic land use. Cesium anomalies provide additional evidence for runoff due to high rainfalls and amplified by anthropogenic impacts. The Petén Itzá core contains anomalous spikes of arsenic and mercury, and these peaks correspond to documented volcanic eruptions and therefore are probably natural. The geochemical composition of sediments and palynological records indicate re‐growth of the forest after ∼900 a BP. This increased forest vegetation coincides with the timing of the decline in Maya agriculture.

Space-Wise approach for airborne gravity data modelling - D. Sampietro; M. Capponi; A. H. Mansi; A. Gatti; P. Marchetti; F. Sansò (Journal of Geodesy, 2017)

The influence of slope on Spartium junceum root system: morphological, anatomical and biomechanical adaptation - Fabio Lombardi; G. S. Scippa; B. Lasserre; A. Montagnoli; R. Tognetti; M. Marchetti; D. Chiatante (Journal of Plant Research, 2017)

Immunocytochemical identification and ontogeny of adenohypophyseal cells in a cave fish, Phreatichthys andruzzii (Cypriniformes: Cyprinidae) - G. Grandi; M. Pezzi; M. G. Marchetti; M. Chicca (Journal of Fish Biology, 2017)
The morphogenesis of the pituitary gland and the chronological appearance of adenohypophyseal cells were investigated for the first time in the Somalian cave fish Phreatichthys andruzzii by immunocytochemistry. The adult adenohypophysis contained: a rostral pars distalis, with prolactin ( PRL ) cells arranged in follicles and adrenocorticotropic ( ACTH ) cells, a proximal pars distalis with somatotropic ( GH ), β‐thyrotropic ( TSH ), β‐gonadotropic type I ( FSH ) and type II ( LH ) cells and a pars intermedia with α‐somatolactin ( SL ), α‐melanotropic ( MSH ) and β‐endorphin ( END ) cells. All regions were deeply penetrated by neurohypophyseal branches. At hatching (24 h post‐fertilization) the pituitary was an oval cell mass, close to the ventral margin of diencephalon. The first immunoreactive cells appeared as follows: PRL at 0·5 days after hatching (dah), GH and SL at 1·5 dah, END at 2 dah, TSH , ACTH and MSH at 2·5 dah, FSH at 28 dah and LH at 90 dah. The neurohypophysis appeared at 5 dah and branched extensively inside the adenohypophysis at 130 dah, but there was no boundary between rostral pars distalis and proximal pars distalis at this stage. The potential indices of prolactin and growth hormone production increased until 28 and 60 dah, respectively. The potential index of growth hormone production correlated positively with total length. Activity of PRL and GH cells, measured as ratio of cell area to nucleus area, was significantly higher in juveniles than in larvae.

GTE: a new software for gravitational terrain effect computation: theory and performances - D. Sampietro; M. Capponi; D. Triglione; A. H. Mansi; P. Marchetti; F. Sansò (Pure and Applied Geophysics, 2016)

Streptococcus salivarius by nasal spray for recurrent otitis: how good is the evidence? - S. Di Mario; V. Basevi; R. D’Amico; C. Gagliotti; M. Gangemi; F. Marchetti; M. L. Moro; G. Tamburlini (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

First mapping of the main high conservation value forests (HCVFs) at national scale: The case of Italy - M. Maesano; B. Lasserre; M. Masiero; D. Tonti; M. Marchetti (Plant Biosystems, 2016)

Dynamics of the silver fir ( Abies alba Mill.) natural regeneration in a mixed forest in the Central Apennine - G. Santopuoli; B. Lasserre; P. Di Martino; M. Marchetti (Plant Biosystems, 2016)

A simple multivariate analysis to assess diversity in a complex long-term managed forest area in central Italy - U. Chiavetta; B. Lasserre; P. Di Martino; M. Marchetti (Plant Biosystems, 2015)

Implementing REDD+ in Papua New Guinea: Can biodiversity indicators be effectively integrated in PNG's National Forest Inventory? - G. Grussu; F. Attorre; D. Mollicone; P. Dargusch; A. Guillet; M. Marchetti (Plant Biosystems, 2014)

Mountain vegetation at risk: Current perspectives and research reeds - C. Palombo; M. Marchetti; R. Tognetti (Plant Biosystems, 2014)

Is land abandonment affecting forest dynamics at high elevation in Mediterranean mountains more than climate change? - C. Palombo; G. Chirici; M. Marchetti; R. Tognetti (Plant Biosystems, 2013)

Carbon sequestration by forests in the National Parks of Italy - M. Marchetti; L. Sallustio; M. Ottaviano; A. Barbati; P. Corona; R. Tognetti; L. Zavattero; G. Capotorti (Plant Biosystems, 2012)

A CAD/CAM-prototyped anatomical condylar prosthesis connected to a custom-made bone plate to support a fibula free flap - L. Ciocca; S. Mazzoni; M. Fantini; F. Persiani; P. Baldissara; C. Marchetti; R. Scotti (Medical & Biological Engineering & Computing, 2012)

Do National Parks play an active role in conserving the natural capital of Italy? - G. Capotorti; L. Zavattero; I. Anzellotti; S. Burrascano; R. Frondoni; M. Marchetti; M. Marignani; D. Smiraglia; C. Blasi (Plant Biosystems, 2012)

Comparison of forest stand structure and management of silver fir–European beech forests in the Central Apennines, Italy and in the Dinaric Mountains, Slovenia - F. Lombardi; M. Klopcic; P. Di Martino; R. Tognetti; G. Chirici; A. Boncina; M. Marchetti (Plant Biosystems, 2012)

Anthraquinone distribution in the hypogeal apparatus of Rubia peregrina L. growing wild in Sardinia - M. Usai; M. Marchetti (Natural Product Research, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Multi‐taxon and forest structure sampling for identification of indicators and monitoring of old‐growth forest - C. Blasi; M. Marchetti; U. Chiavetta; M. Aleffi; P. Audisio; M. M. Azzella; G. Brunialti; G. Capotorti; E. Del Vico; E. Lattanzi; A. M. Persiani; S. Ravera; et al. (Plant Biosystems, 2010)

Linking taxonomical and functional biodiversity of saproxylic fungi and beetles in broad‐leaved forests in southern Italy with varying management histories - A. M. Persiani; P. Audisio; D. Lunghini; O. Maggi; V. M. Granito; A. B. Biscaccianti; U. Chiavetta; M. Marchetti (Plant Biosystems, 2010)

Patterns and trends in tropical forest cover - R. Drigo; B. Lasserre; M. Marchetti (Plant Biosystems, 2009)

Influence of biochemical, mineral and morphological features of natural food on tropical cladocerans - Claudia Fileto; Marlene S. Arcifa; Juliana M. Marchetti; Izabel C. Turati; Norberto P. Lopes (Aquatic Ecology, 2007)

Outlining multi-purpose forest inventories to assess the ecosystem approach in forestry - P. Corona; M. Marchetti (Plant Biosystems, 2007)

ForestBIOTA data on deadwood monitoring in Europe - D. Travaglini; A. Barbati; G. Chirici; F. Lombardi; M. Marchetti; P. Corona (Plant Biosystems, 2007)

A forest typology for monitoring sustainable forest management: The case of European Forest Types - A. Barbati; P. Corona; M. Marchetti (Plant Biosystems, 2007)

Histology and carbohydrate histochemistry of the alimentary canal in the rainbow trout Oncorhynchus mykiss - L. Marchetti; M. Capacchietti; M. G. Sabbieti; D. Accili; G. Materazzi; G. Menghi (Journal of Fish Biology, 2006)
A histological and histochemical analyses were carried out on the entire alimentary canal of the rainbow trout Oncorhynchus mykiss . In particular the oesophageal region showed presence of terminal β‐D‐galactose(1–3)‐N‐acetylgalactosamine and α‐N‐acetylgalactosamine. In the anterior and posterior regions of the stomach, lining epithelium and gastric pits exhibited the presence of β‐gal and α‐GalNAc. In addition sialoglycoconjugates having sialic acid–β–galactose(1–3)‐N‐acetylgalactosamine and sialic acid‐N‐acetylgalactosamine as terminal tri‐ and di‐saccharides, were demonstrated. In proximal and distal intestine goblet cells showed the presence of sialoglyconjugates, having sialic acid‐β‐gal(1–3)‐GalNAc and sialic acid‐GalNAc as terminal sequences, belonging to N‐linked chains. In the enterocytes of the entire intestine, terminal GlcNAc, α‐Gal, α‐fucose were found.

Prostaglandins differently regulate FGF-2 and FGF receptor expression and induce nuclear translocation in osteoblasts via MAPK kinase - Maria Giovanna Sabbieti; Luigi Marchetti; Maria Gabriella Gabrielli; Maura Menghi; Stefano Materazzi; Giovanna Menghi; Lawrence G. Raisz; Marja M. Hurley (Cell and Tissue Research, 2005)

Early antibiotic treatment of pseudomonas aeruginosa colonisation in cystic fibrosis: a critical review of the literature - Federico Marchetti; Luisella Giglio; Manila Candusso; Dino Faraguna; Baroukh M. Assael (European Journal of Clinical Pharmacology, 2004)

Molecular markers linked to the blast resistance gene Pi-z in rice for use in marker-assisted selection - C. A. Conaway-Bormans; M. A. Marchetti; C. W. Johnson; A. M. McClung; W. D. Park (Theoretical and Applied Genetics, 2003)

Mapping QTLs for field resistance to the rice blast pathogen and evaluating their individual and combined utility in improved varieties - R. Tabien; Z. Li; A. Paterson; M. Marchetti; J. Stansel; S. Pinson (Theoretical and Applied Genetics, 2002)

Immnunohistochemical detection of phthalate esters in the alimentary canal of Tilapia spp. - G. Menghi; M. G. Sabbieti; M. Menghi; A. Roda; S. Materazzi; L. Marchetti (Journal of Fish Biology, 2002)
An examination of the occurrence and distribution of phthalate esters in the alimentary canal of a polyhybrid of Tilapia gave evidence of different and selective patterns of distribution in the organ tissues: the phthalate esters were shown to be concentrated in the stomach and anterior intestine. The restricted distribution of phthalate esters can have implications for the physiology of the digestive system. The phthalates, stored in the oxyntic cells of the gastric tubular glands, probably interfere with the digestive process. The strategic location of the enterocytes in the anterior intestine implies that they can hamper the reabsorption of digestion products. The endocrine disrupting effects known for these chemicals are probably related to the absorption of them via the alimentary canal.

The physiological demands of sail pumping in Olympic level windsurfers - Vogiatzis I.; G. De Vito; Rodio A.; Madaffari A.; Marchetti M. (European Journal of Applied Physiology, 2002)

Linear and non-linear analysis of surface electromyograms in weightlifters - F. Felici; A. Rosponi; P. Sbriccoli; G.C. Filligoi; L. Fattorini; M. Marchetti (European Journal of Applied Physiology, 2001)

Mapping of four major rice blast resistance genes from ’Lemont’ and ’Teqing’ and evaluation of their combinatorial effect for field resistance - R. E. Tabien; Z. Li; A. H. Paterson; M. A. Marchetti; J. W. Stansel; S. R. M. Pinson; W. D. Park (Theoretical and Applied Genetics, 2000)

Soybean Kunitz, C-II and PI-IV inhibitor genes confer different levels of insect resistance to tobacco and potato transgenic plants - S. Marchetti; M. Delledonne; C. Fogher; C. Chiabà; F. Chiesa; F. Savazzini; A. Giordano (Theoretical and Applied Genetics, 2000)

Foraging interactions among three benthic fish in a Posidonia oceanica reef lagoon along the Tyrrhenian Coast - M. De Pirrott; G. M. Marchetti; G. Chelazzi (Journal of Fish Biology, 1999)
Three benthic predators Coris julis, Symphodus cinereus and Mullus surmuletus in a Posidonia oceanica reef lagoon of the Tyrrhenian coast had a broad diet, including hard‐bodied invertebrates such as crustaceans and molluscs, but revealed consistent interspecific differences. Diet overlap was greater between C. julis and M. surmuletus in comparison to other combinations. All three species were diurnal feeders, but with diVerent daily patterns of foraging based on diVerent prey availability. There was a general spatio‐temporal correlation in non‐foraging activity among the three species, but foraging activity was correlated only between C. julis and the other two species, but not between S. cinereus and M. surmuletus .There was heterospecific aggregation during foraging between C. julis and M. surmuletus , and possibly a scrounger–producer relationship between them. Fights between C. julis specimens related to foraging activity were common, but not between species. These results support the view that diVerences in spatio‐temporal organization of activity, and interactions during foraging, can contribute to resource partitioning among syntopic populations of fish belonging to the same trophic group.

Strong extracellular nuclease activity displayed by barley (Hordeum vulgare L.) uninucleate microspores - M. Vischi; S. Marchetti (Theoretical and Applied Genetics, 1997)